Crystalline core–amorphous shell heterostructures: epitaxial assembly of NiB nanosheets onto PtPd mesoporous hollow nanopolyhedra for enhanced hydrogen evolution electrocatalysis. Issue 18 (27th April 2020) - Deng, Kai; Ren, Tianlun; Xu, You; Liu, Songliang; Dai, Zechuan; Wang, Ziqiang; Li, Xiaonian; Wang, Liang; Wang, Hongjing
Abstract : Crystalline core–amorphous shell heterostructures composed of PtPd mesoporous hollow nanopolyhedra and NiB nanosheets exhibit enhanced electrocatalytic performance toward the hydrogen evolution reaction. Abstract : Engineering the composition and structure of hybrid electrocatalysts based on precious Pt and non-precious metals is of paramount importance for increasing the utilization efficiency of Pt and enhancing their electrocatalytic performance. Here we report the construction of novel crystalline PtPd @ amorphous NiB core–shell heterostructures (c-PtPd@a-NiB CSHs) with crystalline PtPd mesoporous truncated octahedral nanocages (c-PtPd MTONs) as the cores and amorphous NiB (a-NiB) nanosheets as the shells via a three-step strategy. This hybridization, between c-PtPd MTONs and a-NiB nanosheets, leads to increased catalytically active sites, a modulated surface electronic structure, and enhanced hydrophilic properties. With these properties, the as-obtained c-PtPd@a-NiB CSHs exhibit enhanced electrocatalytic activity toward the hydrogen evolution reaction (HER) in an alkaline medium, with a small required overpotential of 31 mV (@-10 mA cm −2 ), a low Tafel slope of 40.9 mV dec −1, and excellent long-term catalytic durability.